Bedaquiline in the treatment of multidrug- and extensively drug-resistant tuberculosis. Issue 2 (3rd December 2015) - Pym, Alexander S.; Diacon, Andreas H.; Tang, Shen-Jie; Conradie, Francesca; Danilovits, Manfred; Chuchottaworn, Charoen; Vasilyeva, Irina; Andries, Koen; Bakare, Nyasha; De Marez, Tine; Haxaire-Theeuwes, Myriam; Lounis, Nacer; et al.
Bedaquiline, a diarylquinoline, improved cure rates when added to a multidrug-resistant tuberculosis (MDR-TB) treatment regimen in a previous placebo-controlled, phase 2 trial (TMC207-C208; NCT00449644). The current phase 2, multicenter, open-label, single-arm trial (TMC207-C209; NCT00910871) reported here was conducted to confirm the safety and efficacy of bedaquiline. Newly diagnosed or previously treated patients with MDR-TB (including pre-extensively drug-resistant (pre-XDR)-TB or extensively drug-resistant (XDR)-TB) received bedaquiline for 24 weeks with a background regimen of anti-TB drugs continued according to National TB Programme treatment guidelines. Patients were assessed during and up to 120 weeks after starting bedaquiline. Of 233 enrolled patients, 63.5% had MDR-TB, 18.9% had pre-XDR-TB and 16.3% had XDR-TB, with 87.1% having taken second-line drugs prior to enrolment. 16 patients (6.9%) died. 20 patients (8.6%) discontinued before week 24, most commonly due to adverse events or MDR-TB-related events. Adverse events were generally those commonly associated with MDR-TB treatment. In the efficacy population (n=205), culture conversion (missing outcome classified as failure) was 72.2% at 120 weeks, and 73.1%, 70.5% and 62.2% in MDR-TB, pre-XDR-TB and XDR-TB patients, respectively. Addition of bedaquiline to a background regimen was well tolerated and led to good outcomes in this clinically relevant patient cohort with MDR-TB. Bedaquiline safety data in a broad patient population treated for drug-resistant TB including XDR-TB (C209 study) http://ow.ly/TcZBh